ANALISIS PERAN GURU DALAM PENERAPAN PENDIDIKAN KARAKTER PADA PEMBELAJARAN BIOLOGI DI SMK NEGERI 1 LOLOMATUA - Halawa, Erik Arisman; Zega, Novelina Andriani; Waruwu, Toroziduhu; Gulo, Hardikupatu (Program Studi Pendidikan Biologi FKIP Unpatti, 2024)
Background: This research is motivated by the researcher's findings on the role of teachers in implementing character education to students at SMK Negeri 1 Lolomatua who are classified as having less effective learning abilities in the learning process. This research aims to: (1) Find out students' abilities in character education in Biology learning at SMK Negeri 1 Lolomatua, (2) Find out the teacher's obstacles in implementing character education in Biology learning at SMK Negeri 1 Lolomatua, (3) Find out the learning outcomes of participants students towards character education abilities in Biology learning at SMK Negeri 1 Lolomatua. Methods: The research method used is a qualitative descriptive approach. The research location is at SMK Negeri 1 Lolomatua, Lolomatua District, South Nias Regency. The research subjects were 17 class X ATPH students. Results: Based on the research results, it shows that: (1) The application of character education in the learning process to determine the ability of students' learning outcomes in the cognitive domain in Biology learning on character values, namely cognitive ability test questions which consist of levels consisting of: knowledge, understanding, application, analysis, evaluation and creation used in the form of essay test questions with a total of 5 questions, (2) The results of students' learning test scores in Biology learning on character values ​​not all reached KKM 65, the average score of the participants students are 60, and the highest score is 70 and the lowest score is 60, (3) Barriers in implementing character education include the availability of media that is not available at school, students who do not understand the material, limited time in implementing learning activities. Conclusion: The results of students' learning test scores in Biology learning on character values ​​did not all reach a KKM of 65, the average score of students was 60, and the highest score was 70 and the lowest score was 60.